GnRHa/Stanozolol Combined Therapy Maintains Normal Bone Growth in Central Precocious Puberty - Zhu, Shunye; Long, Lingli; Hu, Yue; Tuo, Ying; Li, Yubin; Yu, Zhenhua (Frontiers in Endocrinology, 2021)
Background: Gonadotropin-releasing hormone agonist (GnRHa) is the gold standard for the treatment of Central Precocious Puberty (CPP) with progressive puberty and accelerative growth. However, GnRHa treatment was reported to bring to the growth deceleration and prevent growth plate development which lead to height velocity reducing. Stanozolol (ST) has been used to stimulate growth in patients with delayed growth and puberty, nevertheless, the effect and mechanism of ST on CPP with GnRHa treatment are currently unclear. Methods and Results: In the current study, we recorded the following vital observations that provide insights of ST induced chondrogenic differentiation and maintain normal growth plate development: (1) ST efficiently prevented growth deceleration and maintained normal growth plate development in the rodent with GnRHa treatment; (2) ST suppressed the inhibitory effect of GnRHa to promote chondrogenic differentiation; (3) ST induce chondrogenic differentiation through activation of JNK/c-Jun/Sox9 signling pathway; (4) ST promote chondrogenic differentiation and growth plate development through JNK/Sox9 signaling pathway in vivo. Conclusions: ST could resist the inhibitory effect of GnRHa to promote growth plate development in rodent; ST induced chondrogenic differentiation of chondrocytes and maintained growth plate normal development through activation of JNK/c-Jun/Sox9 signaling. These novel finding indicated that ST might act as a potential agent to maintain normal bone growth in CPP with GnRHa treatment.